Santo dan Sultan : Kisah Tersembunyi Tentang Juru Damai Perang Salib / Paul Moses; Penerjemah, Adi Toha; Editor, Mohammad Husnil - MOSES, Paul; ADI Toha; MUHAMMAD Husnil (Pustaka Alvabet, 2013)
xxv, 411 hlm. ; ilus. ; 20cm